Wavelength-shifter coated polystyrene as an easy-to-build and low-cost plastic scintillator detector. (1st April 2023) - Brignoli, A.; Conaboy, A.; Dormenev, V.; Jimeno, D.; Kazlou, D.; Lacker, H.; Scharf, C.; Schmidt, J.; Zaunick, H.G.
Abstract: We studied the light yield of a pure polystyrene slide coated with wavelength-shifter molecules, coupled to a photomultiplier, using β - particles from a 90 Sr source, as a possible easy-to-build, low-cost plastic scintillator detector. Comparison measurements were performed with an uncoated polystyrene slide as well as with uncoated and coated PMMA slides, the latter which can only produce Cherenkov light when being traversed by charged particles. The results with the single (double) coated polystyrene slides show about 4.9 (6.3) times higher detected photon yield compared to the uncoated slide. For comparison, the light yield of a polystyrene-based extruded plastic scintillator material doped with PTP and POPOP was measured as well. The absolute detected light yield motivates future studies for developing easy-to-build, low-cost polystyrene-based plastic scintillator detectors.